PAb01 液晶NMRによる液晶分子のコアの内部回転の研究 - 井上, 香織; 竹内, 浩; 小中, 重弘 (Proceedings of Japanese Liquid Crystal Society Annual meeting, 2000)
Molecular structures and orientation of tolan and trans-azobenzene, which are models of the cores of liquid-crystal molecules, dissolved in liquid crystals have been determined by proton NMR. Spectral analysis is quite difficult for molecules with ten protons. Therefore initial spectral parameters have been obtained by analyzing integral curves by means of genetic algorithm. Final parameters have been determined by least-squares calculations on absorption frequencies. Both compounds take planar molecular structures in liquid crystals. The structure of the phenyl group of each compound is not significantly different from that in the gas phase and in the crystal. The rotational barriers of phenyl groups in liquid crystals are larger than those in the gas phase. This is also the case for biphenyl and phenyl benzoate and is ascribed to environmental effects of liquid crystals.